Zero waste as an economic criterion of efficiency of the mining enterprise’s activity - I. Golik, Vladimir (2019)
When assessing the economic efficiency of economy’s mining sector, the following economic problems are of priority: the state of mineral deposits, the concentration of property, the raw material economy, dependence on world prices for raw materials, volatility and risks, the deficit of foreign investments, and so on. The issues of the economic environment’s volatility and limited financial and economic resources, rationalization of the use of resource determinants of regional development as well as their modernization development factors, the issues of creating a favorable institutional and infrastructural environment are regarded to be urgent. As a tool for the formation of the regional economy is the regional clustering direction and subregional economic systems, the prospects of which are associated with the processes of integration of economic entities. The current stage of development of the Russian economy is positioned as a deep transformation of commodity production according to the radical improvement of technology development.  The addition of potential of chemical energy to the predominantly mining mechanical energy opens up new prospects to be involved in the operation of still inaccessible mineral resources. This process requires the development of other economic efficiency criteria. The proposed criterion for the mining enterprise’s evaluation effectiveness is a priority condition of non-waste production. Environmental damage due to improper use (waste) is differentiated based on the amount and cost of lost metal and mineral ingredients at local, regional, global and hierarchical levels. The damage components and economic efficiency can be determined based on the extent of utilization, costs and technological level of production.